Standort dialogue between government and business in ght context of polycrisis in Germany - Vladislav B. Belov (Научно-аналитический вестник Института Европы РАН)
By the end of 2024, Germany’s economic and political environment has continued to suffer a decline in competitiveness due to a series of overlapping crises. The risk of productive factors exiting the country has increased, a process commonly referred to as the «deindustrialization of the economy». This development impacts the interests of all key stakeholders involved in the formation of Germany’s Standort product – the nation’s economic-political and socio-economic space competing globally, especially with the United States and China. Both the government and business, represented by interest groups, are motivated to counteract these adverse trends by retaining capital and labor within Germany’s economic territory, as well as attracting them from other economic locations. Success in this endeavor largely depends on their interaction, rooted in dialogue and constructive exploration of Standort-related tools and policies. This article represents the first in domestic scientific literature to analyze the current interaction between Germany’s executive branch and business interest groups, aimed at steering the German Standort out of its polycrisis state and restoring its competitiveness. The article evaluates the effectiveness of these interactions and the potential for implementing the agreements reached.